2018
DOI: 10.1007/s00264-018-3928-5
|View full text |Cite
|
Sign up to set email alerts
|

Which is the optimal orthogeriatric care model to prevent mortality of elderly subjects post hip fractures? A systematic review and meta-analysis based on current clinical practice

Abstract: Elderly patients with hip fracture admitted early into any sort of orthogeriatric models or more specifically to a dedicated orthogeriatric ward had reduced long-term mortality. This study has to be completed by RCT showing the efficacy of orthogeriatric ward compared to other models using outcomes such as quality of life or functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(76 citation statements)
references
References 30 publications
7
69
0
Order By: Relevance
“…At first, one-year mortality was significantly reduced in patients being treated in the OGC unit compared to CTC. These results are in accordance with existing investigations on the impact of OGC and appear to be one of the major benefits attributed to OGC [12,14,[22][23][24]. Only 5 years ago comparative trials on the impact of orthogeriatic treatment on long-term mortality stated, that no significant differences were found in between the groups, while the number of comparative trials taken into account at that time was limited with relatively small study groups [11].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At first, one-year mortality was significantly reduced in patients being treated in the OGC unit compared to CTC. These results are in accordance with existing investigations on the impact of OGC and appear to be one of the major benefits attributed to OGC [12,14,[22][23][24]. Only 5 years ago comparative trials on the impact of orthogeriatic treatment on long-term mortality stated, that no significant differences were found in between the groups, while the number of comparative trials taken into account at that time was limited with relatively small study groups [11].…”
Section: Discussionsupporting
confidence: 89%
“…Only 5 years ago comparative trials on the impact of orthogeriatic treatment on long-term mortality stated, that no significant differences were found in between the groups, while the number of comparative trials taken into account at that time was limited with relatively small study groups [11]. A more recent meta-analysis conducted by Moyet et al showed that patients with hip fracture in the aging population admitted early into any sort of orthogeriatric models or more specifically to a dedicated orthogeriatric ward had reduced long-term mortality, while the authors also claimed, that randomised controlled trials on that topic are still missing [24]. Therefore, similar to hip replacement registries, there is a growing need for registries focusing trauma patients in the aging population such as the orthogeriatric trauma registry founded by the german trauma society (AltersTraumaRegister-DGU®).…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the mortality rate remains between 20% and 30% in the year following a hip fracture. [17,18] We detected that a total of 4 patients had wound infection, 12 patients had the screw cut-out, 7 patients had heterotopic ossification, 11 patients had malunion or nonunion, 1 had a periprosthetic fracture, 1 had implant failure, and 1 had osteolysis with well-fixed implants in the follow-up process. There was no statistically significant difference between the groups in terms of these complications.…”
Section: Discussionmentioning
confidence: 98%
“…FLSs comprise a multidisciplinary team members who together ensure people experiencing a fracture receive correct management and follow‐up . Other models of care, such as orthogeriatric care for patients with hip fracture, were shown to reduce mortality and morbidity compared with standard care . Fracture registries also provide valuable information that can be used to ensure care providers are delivering the best evidence‐based care …”
Section: Pharmacologic Managementmentioning
confidence: 99%